Digital Dependency and Evolution of Identity in Megan Angelo’s Followers - S.S. Sindhuja; Dr. S. Mohanasundari (International Journal of Scientific Research in Science and Technology, 2024)
The drastic development of technologies in this digital world has a significant approval and acceptance by the people. Human beings are embedded themselves in the world in which it is hard to separate their true self and digital self. At first people are crazy about the fame and followers, the aftermath is quite ridiculous. It becomes difficult for the humans to cope up with the private and public life once they tend to immerse themselves deeply into it. This is because the identity they framed for the online platform mingles with the real one forming an interconnectedness. There arises the question of privacy, authenticity and self-presentation. The more and more the world becomes handy, less and less it is secure and safe. The characters in the novel face the similar situation where they are obsessed with digital media and are under the threat of it. They are like trapped figures under the domination of technological tools and are searching for their identities. This research paper tries to highlight the identities of the existent and future human persona through the lens on how the dependence on digital and social media shapes one’s self with reference to the characters in the dystopian novel Followers by Megan Angelo. The surveillance and control of the digital world has tend the characters to frame a mixed and a hybrid identity which they are unaware of.
Keywords: Digital dependency; Digital media; Fame; Identity; Hybridity